2013
DOI: 10.1073/pnas.1215779110
|View full text |Cite
|
Sign up to set email alerts
|

Latent TGF-β binding protein 4 promotes elastic fiber assembly by interacting with fibulin-5

Abstract: Elastic fiber assembly requires deposition of elastin monomers onto microfibrils, the mechanism of which is incompletely understood. Here we show that latent TGF-β binding protein 4 (LTBP-4) potentiates formation of elastic fibers through interacting with fibulin-5, a tropoelastin-binding protein necessary for elastogenesis. Decreased expression of LTBP-4 in human dermal fibroblast cells by siRNA treatment abolished the linear deposition of fibulin-5 and tropoelastin on microfibrils. It is notable that the add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(152 citation statements)
references
References 51 publications
5
144
0
Order By: Relevance
“…As a modifier, Ltbp4 acts to stabilize the sarcolemma, and may work through both direct and indirect effects. LTBP4 has TGFβ-independent effects on the extracellular matrix, and proteolytic cleavage of LTBP4 could generate fragments that could directly contribute to inflammation (43, 44). The extracellular matrix and the sarcolemma are tightly coupled to stabilize and protect muscle from contraction-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…As a modifier, Ltbp4 acts to stabilize the sarcolemma, and may work through both direct and indirect effects. LTBP4 has TGFβ-independent effects on the extracellular matrix, and proteolytic cleavage of LTBP4 could generate fragments that could directly contribute to inflammation (43, 44). The extracellular matrix and the sarcolemma are tightly coupled to stabilize and protect muscle from contraction-induced damage.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we cannot exclude the possibility that LTBP-3 has TGFβ-independent functions that participate in aortic pathology. TGFβ-independent activities have been identified for LTBP-4 in stabilizing microfibril bundles and regulating elastic fiber assembly and for LTBP-2 in the development of ciliary zonule microfibrils (36)(37)(38). Thus, LTBP-3 might directly contribute to the integrity of the matrix or the mechanical compliance of the aortic wall (39).…”
Section: Discussionmentioning
confidence: 99%
“…[5,9,10] Additionally, the interaction between fibulin-5 and LTBP2 and LTBP4 in elastic fiber assembly is important, and LTBP4 was suggested as a potential therapeutic target for regeneration of elastic fibers in vivo. [11,12] Hirai and colleagues demonstrated that the presence of fibulin-5 protein is necessary for elastic fiber assembly in vitro, and, by comparing skin samples from old and young mice, they identified a cleaved protein form of fibulin-5 that was more prominent in old mice. [13] In subsequent in vitro experiments, they showed that serine proteases can cleave fibulin-5, which results in this cleaved nonfunctional fibulin-5 protein.…”
Section: Fibulin-5 Elastogenesis and Repairmentioning
confidence: 99%